A Student-Centered Active Learning Approach to Teaching Anemias in a Medical Laboratory Science Hospital-based Program...American Society for Clinical Laboratory Science (ASCLS) Clinical Laboratory Educators’ Conference (CLEC), February 25-27, 2016 in Minneapolis, Minnesota. - Zawacki, Ashley; Knutson, Marianne; Keohane, Elaine M. (Clinical Laboratory Science)
The traditional education model involves a teacher-centered environment with students playing a passive role in the education process. An environment where active mortality, and low quality of patient care. Interprofessional education (IPE) is a critical component of a health professions education curriculum in addressing the need for interprofessional collaboration in professional practice. Unfortunately, IPE is not currently embedded into the health professions curricula. The purpose of this qualitative exploratory case study was to explore and describe how clinical laboratory science students at a tertiary university hospital perceive and conceptualize IPE through exposure to IPE in clinical preceptorship and service learning experiences. The data collection and analysis process included multiple interviews, student clinical preceptorship journals, student service learning journals, and a researcher's journal. The constant comparison method (Glaser & Strauss, 1967) was used throughout the study as themes and patterns emerged from the raw data and were discovered. Findings indicated that participants believed that IPE helped reduce professional hierarchy, promoted equality and respect and maximized interprofessional collaboration between the health professions. The results from this study reveal how an interprofessional curriculum can unite the health professions early in their formative years to address the inefficiencies and ineffectiveness of a disjointed health care team that negatively affects health care in the United States today